Carbon Nanotubes Filled with Different Ferromagnetic Alloys Affect the Growth and Development of Rice Seedlings by Changing the C:N Ratio and Plant Hormones Concentrations - Hao, Yi (PLoS One, 2016)
The aim of this study was to investigate the phytotoxicity of thin-walled carbon nanotubes (CNTs) to rice (Oryza sativa L.) seedlings. Three different CNTs, including hollow multi-walled carbon nanotubes (MWCNTs), Fe-filled carbon nanotubes (Fe-CNTs), and Fe-Co-filled carbon nanotubes (FeCo-CNTs), were evaluated. The CNTs significantly inhibited rice growth by decreasing the concentrations of endogenous plant hormones. The carbon to nitrogen ratio (C:N ratio) significantly increased in rice roots after treatments with CNTs, and all three types of CNTs had the same effects on the C:N ratio. Interestingly, the increase in the C:N ratio in roots was largely because of decreased N content, indicating that the CNTs significantly decreased N assimilation. Analyses of the Fe and Co contents in plant tissues, transmission electron microscope (TEM) observations and energy dispersive X-ray spectroscopy (EDS) analysis proved that the CNTs could penetrate the cell wall and the cell membrane, and then enter the root cells. According to the author's knowledge, this is the first time to study the relationship between carbon nanotubes and carbon nitrogen ratio and plant hormones.